On the Stability of Consumer Expectations - Ferber, Robert (The Review of Economics and Statistics, 1955)
HOW stable are consumer expectations? In view of the growing awareness of a relationship between expectations and consumer buying, and the concomitant rising popularity of intentions surveys and attitudinal surveys as indicators of consumer purchases, this question assumes a new importance. To what extent, for example, can attitudes and expectations ascertained at one moment of time be extrapolated six months or a year in advance, as is implicitly done when information of this type is used either alone or in conjunction with other material to predict the future course of expenditures? ' Basic to the use of attitude and expectations data in explaining and predicting human behavior and basic to the design of surveys for obtaining such data is the question of the length of time these data retain their validity. Some light is thrown on this question by data collected during an experimental monthly consumer panel operation conducted by the writer with the aid of the Bureau of Economic and Business Research of the University of Illinois. The results of an analysis of these data as they relate to this question are presented here.